Clinical Implications of a New DDX58 Pathogenic Variant That Causes Lupus Nephritis due to RIG-I Hyperactivation. Issue 2 (19th February 2023) - Peng, Jiahui; Wang, Yusha; Han, Xu; Zhang, Changming; Chen, Xiang; Jin, Ying; Yang, Zhaohui; An, Yu; Zhang, Jiahui; Liu, Zhengzhao; Chen, Yinghua; Gao, Erzhi; et al.
Abstract : Abstract : Significance Statement: Lupus nephritis (LN) is the major cause of death among systemic lupus erythematosus patients, with heterogeneous phenotypes and different responses to therapy. Identifying genetic causes and finding potential therapeutic targets of LN is a major unmet clinical need. We identified a novel DDX58 pathogenic variant, R109C, that leads to RIG-I hyperactivation and type I IFN signaling upregulation by disrupting RIG-I autoinhibition, causing LN, which may respond to a JAK inhibitor. Genetic testing of families with multiple cases of LN that identifies this variant may lead to targeted therapy. Background: Lupus nephritis (LN) is one of the most severe complications of systemic lupus erythematosus, with heterogeneous phenotypes and different responses to therapy. Identifying genetic causes of LN can facilitate more individual treatment strategies. Methods: We performed whole-exome sequencing in a cohort of Chinese patients with LN and identified variants of a disease-causing gene. Extensive biochemical, immunologic, and functional analyses assessed the effect of the variant on type I IFN signaling. We further investigated the effectiveness of targeted therapy using single-cell RNA sequencing. Results: We identified a novel DDX58 pathogenic variant, R109C, in five unrelated families with LN. The DDX58 R109C variant is a gain-of-function mutation, elevating type I IFN signaling due to reduced autoinhibition, which leads to RIG-I hyperactivation, increased RIG-I K63 ubiquitination, and MAVS aggregation. Transcriptome analysis revealed an increased IFN signature in patient monocytes. Initiation of JAK inhibitor therapy (baricitinib 2 mg/d) effectively suppressed the IFN signal in one patient. Conclusions: A novel DDX58 R109C variant that can cause LN connects IFNopathy and LN, suggesting targeted therapy on the basis of pathogenicity.